microRNA-146a Signaling in Alzheimer's Disease (AD) and Prion Disease (PrD) - Lukiw, Walter J. (Frontiers in Neurology, 2020)
The mouse- and human-brain-resident, nuclear factor kappa B (NF-κB)-regulated, micro RNA-146a-5p (miRNA-146a-5p) is an inducible, 22-nucleotide, single-stranded non-coding RNA (sncRNA) easily detected in several brain and immunological cell types, and an important epigenetic modulator of inflammatory signaling and the innate-immune response in several neurological disorders. Among all studied microRNAs, miRNA-146a-5p (typically referred to as just miRNA-146a) has been well characterized and its pathological function in progressive, age-related, and lethal human inflammatory neurodegenerative disease states is well documented. This communication will review our current understanding of miRNA-146a, its induction by the NF-kB-stimulating actions of inflammatory mediators, including the secretory products of certain microbial species such as viral vectors, and Gram-negative bacteria (such as Bacteroides fragilis) that are normal residents of the human gastrointestinal (GI) tract microbiome, and how miRNA-146a appears to contribute to neuro-pathological, neuro-inflammatory, and altered neuro-immunological aspects of both Alzheimer's disease (AD) and prion disease (PrD).